Emotional Intelligence Management Improvement Effects: Enhancing Employees’ Performance in the State Owned Hotels in Egypt - Tawfik, Yasser Tawfik Halim; Emara, Ola Abdel Moneim El Sayed (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2018)
With positive keenness and compliance to the target that the hospitality market expertly recover, and, as the Holding company for Tourism and Hotels (HOTAC) exert efforts to accelerate market growth, employees’ adherence to high performance becomes essential. These potentials for performance are expected to prevail with developed managers’ competencies. Here, an emotionally intelligent manager is expected to push towards employees’ positive and committed compliance to goals, and to help to capture higher industry performance levels. This paper investigates the effect of managers’ emotional intelligence on employees’ satisfaction, performance, and reduced emotional exhaustion, applying on the hospitality industry in Egypt, and following the line of study that considers emotional intelligence a significant factor towards the betterment of the workplace environment. Here, emotional intelligence is expected to have an efficacious impact on the organization’s performance, especially when it comes to job satisfaction and employee performance, which are aspects that are considered to influence the overall sector performance. RESEARCH LIMITATIONS The results of the research were based on a limited survey that has been distributed to department managers of three hotels located in Greater Cairo, Egypt (Cairo Marriott Hotel & Omar Khayyam Casino, Marriott Mena House Cairo Hotel, and The Nile Ritz Carlton Hotel). The research targeted state owned hotels run under international hotel chains. It is recognized that further research is necessary to establish the exact nature of the causal linkages between emotional intelligence and performance outcomes in the Egyptian state owned hotels, and further assess the impact of such a concept on sustaining a competitive advantage, and maintaining greater chance for sector growth.
Keywords: الفنادق -- الأداء الوظيفي -- الرضا الوظيفي -- الذكاء العاطفي -- مصر